Pengaruh Pengawasan Kinerja terhadap Produktivitas Kerja di Biro Umum Badan Narkotika Nasional - Ahmad Dzaki Hidayat; Ihsana Elkhuluqo (Universitas Muhammadiyah Prof. DR. HAMKA, 2017)
The research intended to know the effects of performance supervision toward job productivity at General Bureau of National Narcotics Agency. The population of the research were all staffs at this section. The sample were 74 staffs acquired by disproportionate random sampling. The research used associative quantitative methods. After the data tested by normality test and homogeinity test, then the analysis of variances conducted. The result of linear regression showed that and ANAVA calculation showed that Fcount < Ftable (1.62, < 1.80). The hypotesis tested by Pearson’s product moment corelation test and gained rxy = 0.600. This mean that there was a significant effect of performance supervision toward job productivity as compared by coefficient correlation interpretation table. The research concluded that there was a significant effect of performance supervision toward job productivity.